(untitled) (Global Journal of Medical Research, 2016)
Interprofessional working (IPW) is an essential part of the health service delivery system. Effective delivery of health services relies on the contribution of healthcare professionals (HCPs) from all groups. The aim of the study is to examine how HCPs collaborate and to assess their perceptions of IPW on healthcare delivery. This study follows a qualitative research approach. It was conducted in three hospitals in Nepal using semi-structured interview schedule. Purposive sampling method was used to select the hospitals and the participants. All together thirty-eight HCPs participated in the research. This study suggests that IPW is an integral part of HCPs’ life and they viewed it as a booster to support them to deliver the optimal and desired health outcomes. HCPs perceived that organisational support and involvement of service users are important for the successful delivery IPW. Verbal means of communication are mostly used during IPW. Nursing and allied health professionals (AHPs) are more critical to the medical professionals because they feel domination and professional isolation from the medical professionals. This study recognises factors that support IPW and also identifies various barriers to IPW in Nepalese hospitals.